Redno zmanjšanje osnovnega kapitala delniške družbe - Drnovšek, Gregor (Podjetje in delo, 2013)
Two important elements of Regular Share Capital decrease are being scrutinized: purpose and the amount of the reduction. With respect to the latter the combination of Share Capital decrease and Shareholders' voluntary contributions are also being discussed. Besides that the article focuses also on the characteristics of the assets that can be paid out on the basis of the Share Capital decrease, and on the payment ban.
Keywords: delniške družbe; osnovni kapital; spremembe